Transformational leadership, organizational citizenship behaviour and school effectiveness in primary schools, Selangor, Malaysia - Talebloo, Baharak (2015)
The current study is an attempt to explore relationship between transformational leadership, organizational citizenship behaviour, and school effectiveness in primary schools in Selangor, Malaysia based on teachers‟ perception. This study also investigates the level of transformational leadership, organizational citizenship behaviour, school effectiveness and their differences based on school type and location. According to the literature review, number of studies on school effectiveness in Malaysian primary schools is still low. Besides, more investigation is required on the dimensionality of transformational leadership and organizational citizenship behaviour in school to identify their contribution to school effectiveness. Leithwood (1994) model of transformational leadership with associated Leithwood & Jantzi (1995) questionnaire, Organ (1988) model of organizational citizenship behaviour with associated questionnaire by Podsakoff et al. (1990), and seven correlates of effective school model by Lezotte (1997) based on Lezotte & Snyder (2011) correlates of effective school questions were applied for data collection. This study utilized stratified random sampling method by choosing 72 primary schools and 490 teachers with the response rate of (n=410) in 6 districts of Selangor state (Gombak, Hulu Langat, Hulu Selangor, Klang, Kuala Langat and Kuala Selangor) and from three types of National,National type Chinese and National type Tamil school based on their urban and rural locations. Data analysis conducted by using descriptive statistic, analysis of one-way ANOVA, independent t-test, coefficient correlation and Structural Equation Modelling (SEM). Moreover, confirmatory factor analysis (CFA) was done to better fit the model. Reliability and validity analysis (content, construct, convergent, and discriminant) were conducted to confirm that the instrument is valid as well as reliable. The result of descriptive analysis showed that the level of transformational leadership,organizational citizenship behaviour and school effectiveness dimensions were at high level in primary schools in Selangor based on teachers‟ perception. The result of this study showed that, out of eight dimensions of transformational leadership, only two dimensions shows significant difference. First, dimension of “providing individualized support” is significantly higher in Chinese National Type schools compared to Tamil National Type schools; and second, “strengthening school culture” dimension is significantly higher in urban compared to rural schools. Out of the five dimensions of organizational citizenship behaviour dimensions “civic virtue” behaviour by teachers is significantly higher in National schools compared to Chinese National Type schools. The finding also showed that there is no significant difference between organizational citizenship behaviour dimensions based on school location. The result showed that the level of school effectiveness is significantly higher in National schools compared to Chinese National Type schools. The level of “monitoring of students‟ progress” is significantly higher in National compared to Chinese and Tamil schools and “opportunity to learn and time on task” dimension is significantly higher in National compared to Chinese schools. The result of correlation analysis indicated that, there is a positive, significant and high relationships between transformational leadership dimensions and overall school effectiveness. As well, positive, significant, and moderate relationships were found between organizational citizenship behaviour dimensions and overall school effectiveness. The result of SEM indicated that the significant predictors of overall school effectiveness included two dimensions of transformational leadership (shared vision and models behaviour), and three dimensions of organizational citizenship behaviour (altruism, conscientiousness and civic virtue) which accounted for 62% of variance in overall school effectiveness. Moreover, overall transformational leadership and organizational citizenship behaviour collectively, accounted for 57% of variance in overall school effectiveness. This study proposed several recommendations to the Ministry of Education, headmasters, teachers, and school administrators, to improve the level of school effectiveness by practicing transformational leadership dimensions especially “building shared vision” and “models behaviour” dimension. Moreover, they can develop, maintain, and elevate the level of school effectiveness by exhibiting civic virtue, altruism, and conscientiousness behaviours as the dimensions of organizational citizenship behaviour in primary schools in Selangor, Malaysia.